Academic Integrity in Higher Education: Understanding and Addressing Plagiarism - Mulenga, Robert; Shilongo, Helvi (Tecno Scientifica Publisher, 2024)
This article delves into the profound implications of plagiarism, extending beyond its role as an academic transgression to challenge the foundational principles of truth, originality, and integrity upon which the academic world is built. Plagiarism's extensive consequences ripple through students, educators, and educational institutions, posing a substantial threat to the integrity of the educational system. The primary aim of this study is to comprehensively address the complexities of plagiarism in higher education, emphasizing the need for effective strategies to safeguard and promote academic integrity. Academic institutions, designed to cultivate knowledge and character development, confront the unsettling presence of plagiarism, necessitating an in-depth exploration of its multifaceted causes and motivations for meaningful mitigation. The study identifies academic pressure, time constraints, lack of knowledge about citation rules, and the digital age as significant contributors to the prevalence of plagiarism. It underscores the far-reaching consequences of this issue and highlights the pivotal role of prevention and detection strategies, notably plagiarism detection software such as Turnitin, Grammarly, and Copyscape, in the ongoing battle to preserve academic honesty and the sanctity of scholarly work.